AUDITING OF PRESCRIPTION TO STUDY THE DRUG UTILIZATION PATTERN IN POST-OPERATIVE PATIENTS IN GENERAL SURGERY WARDS: A STUDY AT A TERTIARY CARE HOSPITAL - SNEHA BHATAIA,; S.K.MATHUR,; SANJAY SANKHLA,; MAHESH KUMAR,; MUKESH SHARMA, (International Journal of Pharma and Bio Sciences, 2016)
This study was planned to evaluate the prescribing and drug utilization pattern in the post-operative patients in wards of the General Surgery Department of J.L.N. Hospital Ajmer. I. A total of 630, patients’ prescriptions/ case record forms were collected over a period of 6 months from the medical record room for analysis and rationalization. . Average number of drugs prescribed was 8.93. The most commonly used drugs were antimicrobials (28.85%), nearly followed by GIT drugs (26.05%). Among the 5627 medicine formulations prescribed, 98.51% ) were prescribed by /generic names, 61.92% of total medicine formulations, were from the, WHO Model List of Essential Medicines (EML) whereas 78.99% of total medicine formulations, were listed in National Model List of Essential Medicines (NLEM). Polypharmacy was observed. Most drugs prescribed were AMAs, GIT related, Intravenous fluids 872(15.50%) NSAIDs (09.14%), CNS drugs(08.46%), Enzymes(01.79%) and Multivitamins and trace elements(05.63%). Percentage of medicines prescribed from EDL found to be less. . Most of the drugs were prescribed by generic name; this indicates the good prescription habit. Prescribing medicines by official names avoids the confusion and makes the drug therapy rational and cheaper. The proportion of prescription containing antimicrobials was quite high in the present study.